Cardioprotective Effect of Apigenin-Hydroxyapatite Nanocomposite against H2O2-Induced Injury in Cardiomyoblast Cells - Makeen, Hafiz; Albratty, Mohammad (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Cardiovascular diseases remain the leading cause of mortality worldwide, largely driven by oxidative stress and inflammation during myocardial ischemia and reperfusion injury. Apigenin, a natural flavonoid, exhibits potent antioxidant and anti-inflammatory properties but suffers from poor solubility and bioavailability. To overcome these limitations, a novel Apigenin-Hydroxyapatite Nanocomposite (Api-HANPs) was developed to enhance its therapeutic efficacy against oxidative cardiac injury. Materials and Methods: Api-HANPs were synthesized via a green mechanochemical approach and characterized using FTIR, XRD, and FESEM analyses to confirm composite formation and structural morphology. The cardioprotective potential of Api-HANPs was evaluated in H9c2 cardiomyoblast cells exposed to Hydrogen Peroxide (H₂O₂)- induced oxidative stress. Cytotoxicity, antioxidant enzyme activities (SOD, CAT), lipid peroxidation (MDA), intracellular Reactive Oxygen Species (ROS) levels, apoptosis (AO/EB, DAPI), and mitochondrial membrane potential (Rh-123) were assessed. Molecular docking was performed to explore apigenin’s binding affinity with the NF-κB protein, and immunofluorescence staining was used to evaluate NF-κB and Nrf2 nuclear translocation. Results: FTIR and XRD confirmed successful integration of apigenin into the hydroxyapatite matrix with altered crystallinity and improved surface morphology. Api-HANPs markedly improved cell viability in a dose-dependent manner, with maximal protection at 50 µM. Pretreatment with Api-HANPs significantly reduced H₂O₂-induced apoptosis, ROS production, and MDA levels while restoring antioxidant enzyme activity and mitochondrial membrane potential (p < 0.0001). Molecular docking revealed a strong binding affinity between apigenin and NF-κB (-7.7 kcal/mol), and immunostaining showed that Api-HANPs suppressed NF-κB nuclear translocation while promoting Nrf2 activation, indicating simultaneous anti-inflammatory and antioxidant actions. Conclusion: The Api-HANPs nanocomposite effectively mitigates oxidative stress-induced cardiomyoblast injury by restoring redox balance, preserving mitochondrial integrity, and modulating NF-κB/Nrf2 signaling pathways. These findings suggest Api-HANPs as a promising nanotherapeutic strategy for preventing oxidative cardiac damage and managing cardiovascular disorders.
Keywords: Apigenin; Cardiovascular Disease; Hydroxyapatite; Myocardial Injury; Cardiomyoblast